INCOHERENCE AND CONTRADICTION IN THE VALUES CLARIFICATION MOVEMENT - Ryan, William L. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
From the beginning the Values Clarification movement of Raths, Harmin, and Kirchenbaum was characterized as amoral, subjectivist, inconsistent, and relativist. Later, attempts have been made to modify the movement to make it a nonjudgmental, nondogmatic, and nonindoctrinative substitute for moral education. The claim that the correct use of the process of Values Clarification could result in certain general, positive virtues and attitudes has not been validated, nor has the approach become more coherent or less relativistic. Ad hoc attempts to compensate for the original confusion have not proved to be successful. RÉSUMÉ Dès le début, le mouvement d'éclaircissement des valeurs de Raths, Harmin et Kirchenbaum a été taxé d'amoral, subjectif, incohérent et relativiste. Par la suite, on a plusieurs fois tenté de transformer le mouvement en ersaatz exempt de jugement, de dogme et de tout caractère endoctrinant de l'enseignement de la morale. L'argument voulant que l'utilisation judicieuse du processus d'éclaircissement des valeurs permette d'acquérir des attitudes et des vertus positives n'a pas été validé pas plus que cette méthode a gagné en cohérence et a perdu en relativisme. Les tentatives officielles visant à pallier la confusion d'origine se sont toutes soldées par un échec.